ALIENATION AS A CENTRAL PHENOMENON OF PSYCHOTRAUMA PROCESS - Mishchuk, Serhiy (PSYCHOLOGICAL JOURNAL, 2019)
The article examines the content of the phenomenon of alienation in the context of its significance in the process of psychotrauma in children. Amplification of psychotramatic process leads to exacerbation of central symptoms up to disruption of socialization and appearance of separation or alienation. Alienation manifests as strengthening of focus on internal criteria, and losing of ability to understand others intuitively. The child closes for himself the opportunities for self-accomplishment, interaction in social groups, thus further isolating in the internal world. The authors present the results of an empiric research study of the level of psychotrauma among schoolchildren, typical post-traumatic manifestations and symptoms of psychotrauma, processes of adaptation, socialization and posttraumatic growth. In the studies sample (N=345) the PTSD symptoms were found in 87%, and symptoms of exacerbation of psychotrauma (intrusion, avoidance, hyper-reaction) in 83%. The assessment processes of adaptation and socialization in children has shown substantial prevalence of disorders in this area, in 84 and 19%, respectively. The authors performed the analysis of the association between the phenomenon of alienation and successfulness of coping with psychotrauma. The results confirm that the process of alienation associated with adaptation and socialization in children may be mitigated if, and to the extent, the psychotrauma is coped with. These associations characterize the phenomenon falienationasone of important markers of psychotrauma process, whichisre flectingit sexacerbationor stalling. Over comingalienation in children helps with over coming of the barrier with the social surrounding, occurringas a result of psychotrauma. Quittingalie nation does not only mitigate symptoms of psychotrauma, but also blocks themechanism of their exacerbationandre-traumatization, and improvessus trainability and higher chance of post-traumatic growth.